A Preliminary Note on Strength Prperties Of Leucaena leucocephala From Lalkua, Tarai Bhabar Forest Division (U.P.) - Shukla, N. K. (Indian Forester, 1982)
Based on physical and mechanical tests conducted on small clear specimens, the strength properties of Leueaena leucocephala in green condition, are reported and compared with Fraxinus micrantha, Morus alba and Tectona grandis. In general Leueaena leucocephala has given slightly lower strength properties except in some cases as compared to above species.